Branching fraction and CP asymmetry of the decays B+ → K0Sπ+ and B+ → K0SK+ - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; De Cian, Michel; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Fontana, Marianna; Gersabeck, Evelina; et al. (Physics letters, 2013)
An analysis of B+→KS0π+ and B+→KS0K+ decays is performed with the LHCb experiment. The pp collision data used correspond to integrated luminosities of 1 fb−1 and 2 fb−1 collected at centre-of-mass energies of s=7 TeV and s=8 TeV, respectively. The ratio of branching fractions and the direct CP asymmetries are measured to be B(B+→KS0K+)/B(B+→KS0π+)=0.064±0.009 (stat.)±0.004 (syst.), ACP(B+→KS0π+)=−0.022±0.025 (stat.)±0.010 (syst.) and ACP(B+→KS0K+)=−0.21±0.14 (stat.)±0.01 (syst.). The data sample taken at s=7 TeV is used to search for Bc+→KS0K+ decays and results in the upper limit (fc⋅B(Bc+→KS0K+))/(fu⋅B(B+→KS0π+))<5.8×10−2 at 90% confidence level, where fc and fu denote the hadronisation fractions of a b¯ quark into a Bc+ or a B+ meson, respectively.
Im Titel sind ""+" und "0" hochgestellt und "S" tiefgestellt
LHCb Collaboration: R. Aaij, O. Aquines Gutierrez, S. Bachmann, A. Bien, J. Blouw, M. Britsch, M. De Cian, A. Di Canto, F. Dordei, C. Färber, M. Fontana, E. Gersabeck, O. Grünberg, S. Hansmann-Menzemer, T. Hartmann, M. Hess, A. Jaeger, K. Kreplin, G. Krocker, B. Leverington, C. Linn, J. Marks, M. Meissner, T. Nikodem, D. Popov, M. Schmelling, P. Seyfert, S. Stahl, J. van Tilburg, U. Uwer, D. Volyanskyy, C. Voß, H. Voss, R. Waldi, S. Wandernoth, D. Wiedner, M. Zavertyaev, A. Zhelezov und weitere 619
Gesehen am 21.04.2021